Applying food systems thinking in recreational fisheries: The case of shore fishing in Detroit, Michigan - Emma D. Rice; Vivian M. Nguyen; Leandro Castello; Mahatub Khan Badhon; Elizabeth A. Nyboer (Marine Policy, 2026)

Assessing social–ecological feedbacks in small-scale fisheries - Leandro Castello; Adriana Guimarães Abreu; George Christopher Brooks; João Vitor Campos-Silva; Priscila dos Reis Cunha; Ayan Santos Fleischmann; Caetano Lucas Borges Franco; Ana Claudia Gonçalves; Emma Ann Hultin; Holly Kathleen Kindsvater; Eduardo Guimarães Martins; Cristina Isis Buck Silva; et al. (Ambio, 2026)
Assessment frameworks do not capture the complexity of the social–ecological dynamics of small-scale fisheries (SSF), which support millions of livelihoods yet face persistent sustainability challenges. Reciprocal feedbacks between fish populations and fishers that are central to sustainability remain insufficiently integrated into assessment approaches because conventional fisheries management emphasizes population dynamics, whereas social–ecological systems research focuses on social drivers and faces operational challenges. We propose an integrative diagnostic approach that explicitly links fish population dynamics with theories of fisher behavior and governance. We illustrate its application using co-managed arapaima fisheries in the Amazon Basin, where sustainability emerges from multi-scalar social and ecological interactions. By capturing these feedbacks, the approach bridges ecological and social dimensions to identify key drivers of sustainability. It provides a replicable, interdisciplinary framework for diagnosing SSF sustainability and identifying leverage points to support adaptive governance across diverse contexts.

Dalbulus maidis (Hemiptera: Cicadellidae) spatio-temporal dynamics and infection prevalence with the corn stunt mollicutes and virus in Santa Catarina, Brazil - Jacson Ferreira; Marcos Vinicius Silva de Andrade; Eduardo Silva Gorayeb; Lilian Katiany Castello Rabello Zinger; Daian Marcos Savaris; Monalisa Cristina de Cól; Emerson Medeiros Del Ponte; Fábio Nascimento da Silva; Leandro do Prado Ribeiro; Maria Cristina Canale (Crop Protection, 2026)

Opportunities to better integrate inland fish and fisheries in multilateral environmental agreements - Abigail J. Lynch; Devin Bartley; T. Douglas Beard, Jr.; Gabriel Borba; Steven J. Cooke; Ian G. Cowx; Vittoria Elliott; Holly Embke; Edith Gondwe; Zeb Hogan; Jonathan G. Low; Jamie C. Madden; et al. (Environmental Science & Policy, 2025)

Comanagement and reconciling of ecological and economic benefits in an Amazonian freshwater fishery - Monalisa R. O. Silva; Leandro Castello; Carolina T. Freitas; João V. Campos‐Silva; Carlos A. Peres; Evlyn M. L. M. Novo (Conservation Biology, 2025)
Freshwater ecosystems contribute substantially to the global fish catch. However, freshwater fisheries face growing human pressures and are underrepresented in global analyses and conservation strategies. Attempts to reconcile conservation and human welfare goals in fisheries have led to comanagement by the government and local communities, along with other stakeholders, but assessments of its effectiveness in freshwater fisheries are lacking. We investigated the effectiveness of comanagement in freshwater fisheries by assessing ecological (fish catch) and economic (fishing revenue) outcomes in a major tributary of the Amazon Basin. Fisheries comanagement in the Amazon is typically implemented through an approach developed by riverine communities called lake management in which floodplain lakes are categorized as open access, subsistence, or protected. Each category has different levels and types of fishing pressure. We analyzed data (e.g., fishing data and management rules) from 1607 fishing trips of 198 fishers over 5 years in 30 riverine communities in 74 floodplain lakes (20 open access, 33 subsistence, and 21 protected). Lake comanagement increased fish catch in protected lakes over time by 12% (2.4 kg) compared with subsistence lakes and by 13% (2.6 kg) compared with open‐access lakes ( p = 0.03). Increased fish catch in protected lakes was mainly due to limits on fishing effort. Fishing revenue was 63% greater in protected lakes than in open‐access lakes ( p

Fishing shrinks the size structure of exploited coral reef fishes in Brazil - Madeline V. Wood; Felipe M. Carvalho; Leandro Castello (Fisheries Research, 2024)

Flood Pulse Effects on the Growth of Pseudoplatystoma fasciatum in the Amazon Basin - Luciana Alves Pereira; Leandro Castello; Eric Hallerman; Edson Rubens Ferreira Rodrigues; Carolina Rodrigues da Costa Doria; Fabrice Duponchelle (Fishes, 2024)
Fish growth is a fundamental biological process driven by a multitude of intrinsic (within-individual) and extrinsic (environmental) factors that underpin individual fitness and population dynamics. Interannual variability in river hydrology regarding the intensity and duration of floods and droughts can induce interannual variations in the biotic and abiotic variables that regulate fish growth. However, the understanding of how interannual variability in river hydrology affects fish growth remains limited for most species and ecosystems. We evaluated how inter-annual hydrological variations within the Amazon River basin influence the growth of the catfish Pseudoplaystoma fasciatum. Our research questions were as follows: Do floods lead to the faster growth of P. fasciatum and droughts lead to the slower growth? And do floods and droughts affect all age classes in the same manner? We sampled 364 specimens of P. fasciatum from five sites in the Amazon basin, estimated their growth rates, and related the growth rates to indices of the intensity of floods and droughts. We fitted linear mixed-effects models to test the relationship between growth increments and hydrological indices (with F and D quantifying the intensities of floods and droughts, respectively), age as fixed effects, and basins and Fish ID as random effects. We found an inverse relationship between the increment width in the fish hard parts and hydrological indices. That is, intense floods and droughts negatively affected the growth rates. We also found that the growth of P. fasciatum was no different in years with intense and mild floods across age classes 1–5, although was different for age class 6. However, the growth of P. fasciatum was faster in years of mild droughts for all age classes. Our results showing that the growth of P. fasciatum was slower in years of intense droughts are supported by those of previous studies in the Amazon basin and elsewhere. However, our results showing for the first time that the growth of P. fasciatum is slower in years of intense flooding is the opposite of patterns found in other studies. These results thus suggest that the growth of P. fasciatum is maximized within an optimum range of hydrological conditions, where neither floods nor droughts are intense.

An approach to assess data-less small-scale fisheries: examples from Congo rivers - Leandro Castello; Felipe Carvalho; Nelly Ornelle Onana Ateba; Alidor Kankonda Busanga; Amy Ickowitz; Emmanuel Frimpong (Reviews in Fish Biology and Fisheries, 2023)
Small-scale fisheries (SSF) account for much of the global fish catch, but data to assess them often do not exist, impeding assessments of their historical dynamics and status. Here, we propose an approach to assess 'data-less' SSF using local knowledge to produce data, life history theory to describe their historical multispecies dynamics, and length-based reference points to evaluate stock status. We demonstrate use of this approach in three data-less SSFs of the Congo Basin. Fishers' recalls of past fishing events indicated fish catch declined by 65–80% over the last half-century. Declines in and depletion of many historically important species reduced the diversity of exploited species, making the species composition of the catch more homogenous in recent years. Length-at-catch of 11 of the 12 most important species were below their respective lengths-at-maturity and optimal lengths (obtained from Fishbase) in recent years, indicating overfishing. The most overfished species were large-bodied and found in the Congo mainstem. These results show the approach can suitably assess data-less SSF. Fishers' knowledge produced data at a fraction of the cost and effort of collecting fisheries landings data. Historical and current data on fish catch, length-at-catch, and species diversity can inform management and restoration efforts to curb shifting baselines of these fisheries. Classification of stock status allows prioritizing management efforts. The approach is easy to apply and generates intuitive results, having potential to complement the toolkits of researchers and managers working in SSF and engage stakeholders in decision-making processes.

-I fish, therefore I monitor: Participatory monitoring to assess inland small-scale fisheries - José Amorim Reis-Filho; Fecundo Ramos-Filho; Leandro Castello; Tommaso Giarrizzo (Environmental Management, 2023)

A Synthesis of the Ecology and Conservation of Pseudoplatystoma Catfishes in the Neotropics - Luciana A. Pereira; Leandro Castello; Donald J. Orth; Fabrice Duponchelle; Eric M. Hallerman (Fishes, 2023)
Species of the genus Pseudoplatystoma, the long-whiskered catfishes, are important in commercial and recreational fisheries in South America, and some species have become key to regional aquaculture. Some species of the genus are under pressure due to overfishing and the negative impacts of dams. Six questions are asked in this review: (i) What species are in the genus, and where are they distributed? (ii) What are the life histories and ecologies of Pseudoplatystoma species? (iii) What are the patterns of somatic growth for these species? (iv) What is known about the biomass, production, and population dynamics of Pseudoplatystoma? (v) What is the geographic distribution of genetic variation within Pseudoplatystoma species? (vi) What are the threats to the conservation of these species? The taxonomy of the genus currently includes eight species, respectively, distributed over the Orinoco, Amazon, Paraná, and São Francisco basins. Pseudoplatystoma catfishes typically exhibit longitudinal migrations for reproduction and lateral migration for feeding, but these patterns may vary among populations. The size of the first maturation of these catfishes varies between 57 cm to 82 cm in total length. Five of the eight species spawn during the rising water season. Pseudoplatystoma species can grow to about 130 cm in total length and 100 Kg in weight and live until 30 years of age, depending upon the species. Biomass production and population dynamics of these catfishes have not yet been fully described. Their life-history characteristics indicate that they are periodic strategists with associated population recruitment dynamics. Population genetic patterning varies among Pseudoplatystoma species, with some degree of homing behavior and genetic differentiation among populations, indicating the need for management by applying the Management Unit and perhaps Evolutionary Significant Unit concepts. The main threats to the persistence of these catfishes are overfishing and alterations in and obstruction of river flow due to the construction of hydropower dams. After synthesizing existing information on species of the genus Pseudoplatystoma, we offer suggestions for future research to fill critical gaps in the knowledge of this group.

The stock assessment theory of relativity: deconstructing the term “data-limited” fisheries into components and guiding principles to support the science of fisheries management - Jason M. Cope; Natalie A. Dowling; Sybrand A. Hesp; Kristen L. Omori; Pia Bessell-Browne; Leandro Castello; Rowan Chick; Dawn Dougherty; Steven J. Holmes; Richard McGarvey; Daniel Ovando; Josh Nowlis; et al. (Reviews in Fish Biology and Fisheries, 2023)

Institutional effects on ecological outcomes of community-based management of fisheries in the Amazon - Caroline C. Arantes; Leandro Castello; Xavier Basurto; Nicole Angeli; Aby Sene-Haper; David G. McGrath (Ambio, 2022)

Correction to: Gear selectivity of functional traits in coral reef fisheries in Brazil - Felipe Carvalho; Leandro Castello; Beatrice Ferreira; Gavin McDonald; Michael Power (Coral Reefs, 2022)

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)

Gear selectivity of functional traits in coral reef fisheries in Brazil - Felipe Carvalho; Leandro Castello; Beatrice Ferreira; Gavin McDonald; Michael Power (Coral Reefs, 2021)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Hydrologic variability effects on catches of Prochilodus nigricans in the lower Amazon - Daniela Barros; Miguel Petrere; Leandro Castello; Paulo Brasil Santos; Davi Butturi-Gomes; Victoria Judith Isaac (Aquatic Sciences, 2021)

Flooding effects on abundance of an exploited, long-lived fish population in river-floodplains of the Amazon - Leandro Castello; Peter B. Bayley; Nidia N. Fabré; Vandick S. Batista (Reviews in Fish Biology and Fisheries, 2019)

Feeding ecology of generalist consumers: a case study of invasive blue catfish Ictalurus furcatus in Chesapeake Bay, Virginia, USA - Joseph D. Schmitt; Brandon K. Peoples; Leandro Castello; Donald J. Orth (Environmental Biology of Fishes, 2019)

Fishery yields vary with land cover on the Amazon River floodplain - Leandro Castello; Laura L Hess; Ram Thapa; David G McGrath; Caroline C Arantes; Vivian F Renó; Victoria J Isaac (Fish and Fisheries, 2018)
Inland fisheries underpin food security in many tropical countries. The most productive inland fisheries in tropical and subtropical developing countries occur in large river–floodplain systems that are often impacted by land cover changes. However, few studies to date have assessed the effects of changes in floodplain land cover on fishery yields. Here, we integrated fisheries and satellite‐mapped habitat data to evaluate the effects of floodplain deforestation on fishery yields in 68 floodplain lake systems of the lower Amazon River, representing a wide range in relative amounts of woody, herbaceous and non‐vegetated land cover. We modelled relative fish yields (fish capture per unit effort [ CPUE ]) in the floodplain lakes as a function of the relative amounts of forest, shrub, aquatic macrophyte and bare/herbaceous habitats surrounding them. We found that forest amount was positively related ( p = .0003) to multispecies CPUE . The validity of these findings was supported by rejection of plausible alternative causative mechanisms involving habitat‐related differences in amount of piscivores, fishing effort, lake area, and habitat effects on CPUE of the nine taxa dominating multispecies yields. Our results provide support to the idea that removal of floodplain forests reduces fishery yields per unit effort. Increased protection of floodplain forests is necessary to maintain the food, income and livelihood security services provided by large river–floodplain fisheries.

Large‐scale degradation of Amazonian freshwater ecosystems - Leandro Castello; Marcia N. Macedo (Global Change Biology, 2016)
Hydrological connectivity regulates the structure and function of Amazonian freshwater ecosystems and the provisioning of services that sustain local populations. This connectivity is increasingly being disrupted by the construction of dams, mining, land‐cover changes, and global climate change. This review analyzes these drivers of degradation, evaluates their impacts on hydrological connectivity, and identifies policy deficiencies that hinder freshwater ecosystem protection. There are 154 large hydroelectric dams in operation today, and 21 dams under construction. The current trajectory of dam construction will leave only three free‐flowing tributaries in the next few decades if all 277 planned dams are completed. Land‐cover changes driven by mining, dam and road construction, agriculture and cattle ranching have already affected ~20% of the Basin and up to ~50% of riparian forests in some regions. Global climate change will likely exacerbate these impacts by creating warmer and dryer conditions, with less predictable rainfall and more extreme events (e.g., droughts and floods). The resulting hydrological alterations are rapidly degrading freshwater ecosystems, both independently and via complex feedbacks and synergistic interactions. The ecosystem impacts include biodiversity loss, warmer stream temperatures, stronger and more frequent floodplain fires, and changes to biogeochemical cycles, transport of organic and inorganic materials, and freshwater community structure and function. The impacts also include reductions in water quality, fish yields, and availability of water for navigation, power generation, and human use. This degradation of Amazonian freshwater ecosystems cannot be curbed presently because existing policies are inconsistent across the Basin, ignore cumulative effects, and overlook the hydrological connectivity of freshwater ecosystems. Maintaining the integrity of these freshwater ecosystems requires a basinwide research and policy framework to understand and manage hydrological connectivity across multiple spatial scales and jurisdictional boundaries.

Potential effects of dam cascade on fish: lessons from the Yangtze River - Fei Cheng; Wei Li; Leandro Castello; Brian R. Murphy; Songguang Xie (Reviews in Fish Biology and Fisheries, 2015)

Environmental influences on the distribution of arapaima in Amazon floodplains - Caroline C. Arantes; Leandro Castello; Mauricio Cetra; Ana Schilling (Environmental Biology of Fishes, 2013)

Lessons from Integrating Fishers of Arapaima in Small-Scale Fisheries Management at the Mamirauá Reserve, Amazon - Leandro Castello; João P. Viana; Graham Watkins; Miguel Pinedo-Vasquez; Valerie A. Luzadis (Environmental Management, 2009)